ANALISIS PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN RELIGIUSITAS ISLAM TERHADAP TINGKAT OCBIP PADA GURU MA DI TEMANGGUNG - Naufalie, Aulia Shofa; Mas’ud, Fuad (Diponegoro Journal of Islamic Economics and Business, 2021)
Quality of teachers are one parameter for determining standard in an education. This will lead teachers to improve their quality to achieve better standards. This study aims to measure the effect of organizational culture, organizational commitment and Islamic religiosity towards OCBIP. The population in this study were 306 teachers of Madrasah Aliyah in Temanggung. Samples were taken as many as 75 respondents with a purposive sampling. The data collection method used in this study was a questionnaire and data testing using the SPSS Statistics 24. Data analysis used was descriptive analysis and multiple linear regression analysis. The results showed that organizational culture, organizational commitment and Islamic religiosity have positive and significant effect on the level of teachers’ OCBIP in Madrasah Aliyah in Temanggung both partially and simultaneously. The coefficient of determination shows that 60% of the dependent variable OCBIP can be stated by the independent variables and the rest 40% explained by another factors outside this study.